Qualitative Research on the Radiation Knowledge Levels of Non-Doctor Healthcare Workers and Developing Qualitative Scale - SARIHAN, Mucize (International Journal of Computational and Experimental Science and Engineering, 2023)
Radiation is used in a wide variety of fields, especially in the health sector. The human cell must be protected from unwanted radiation doses due to its dangerous effect. Employees' knowledge of radiation is important and therefore this level of knowledge must be known. In this study, a semi-structured qualitative questionnaire was used to determine the perception and knowledge levels of healthcare professionals (nurses, technicians) who do not use dosimeters about ionizing and non-ionizing radiation, and to reveal their experience and opinions on the subject. In-depth interviews were made. Qualitative data coding, content analysis (calculation and mapping of relationships between code frequencies, themes and categories) were performed in the MAXQDA 2020 package program with the data obtained after the interview. 20 healthcare personnel participated in the study. From the data obtained, 10 main themes related to the subject were determined. Main themes emerging; "Harms of radiation", "type and properties of radiation", "all imaging devices emit radiation", "principles of radiation protection", "non-ionizing radiation", "infrared rays", "diagnosis and treatment", "radiation doses Radiation emission," Radiation pollution and ionizing radiation "Sub-codes of all these main themes were determined, schemes were created and coded participant views were shown in a cross-table form, semi-structured questions and a qualitative scale were developed.